Potential of Endophytic Fungi as Plant Growth-Promoting Fungi (PGPF) Against Growth of Single Bud Set Seedlings on Sugarcane Plants (Saccharum officinarum L) - Antok Wahyu Sektiono; Novency Habtuti; Yohana Avelia Sandy; Yogo Setiawan (PLANTROPICA: Journal of Agricultural Science, 2023)
Increase of sugarcane productivity must be followed by improvements to a more environmentally sound cultivation system. One of them is the use of endophytes. Endophytic fungi are indeed included in the group of growth-promoting fungi or Plant Growth Promoting Fungi / PGPF and are known to secrete growth hormones such as Indole Acetic Acid (IAA), gibberellin so that they can spur growth. This study aims to determine the type of endophytic fungus that can potentially be PGPF in sugarcane breeding. The research uses sampling methods, exploration, and application of PGPF in sugarcane plants. The results of the identification of endophytic exploration fungi of sugarcane plants obtained five colonies consisting of 4 genera and four species from Trichoderma sp., Aspergillus sp., Penicillium sp., and Fusarium sp. From the results of the potency test, the results were obtained that the soaking of bud set seeds with isolates of the fungus Trichoderma sp., Penicillium sp. Noticeable effect on plant height, stem diameter, and the number of leaves.